Historical Amnesia - Eirik Johannes Irgens (Nordic Journal of Comparative and International Education, 2018)
A number of initiatives have been put forth over the last decade to improve quality in Norwegian schools. Many have been nationwide government-initiated programs. However, several studies express concern about the actual effect of these programs, and some also point to a lack of local anchoring and involvement of teachers. In this article, I draw on studies of one such program. Ungdomstrinn i utvikling (Lower Sec-ondary in Development) was a five-year school-based competence development program in more than 1200 lower-secondary level schools. We found that the local start-up phase and the co-determination of the teach-ers were crucial, and few schools drew on knowledge from the 1960s in Norway on how to organize dia-logue seminars so teachers might have a chance to participate in the local design of the program and estab-lish a shared understanding and knowledge of the challenges at hand. Instead, we found examples of a transaction perspective and an “order and deliver” model of competence development. I discuss this as a possible consequence of the influence of instrumental management theory and why the Nordic cooperation model, even though challenging for school leaders, local union representatives and teachers, would be a better approach to school development. Lastly, I argue that we should avoid historical amnesia and that we would probably be better off if we revived the knowledge from the 1960s and after on co-generation and collaboration.